Cladoceran Diversity within Samarra Impoundment, Iraq - Majeed, Osama S.; Nashaat, Muhanned; Sahar Ahmad Taha; Idrees A.A. Al-Bahathy; Abdeldjalil belkendil (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
This research is considered the first of its kind in this sector of the river for more than three decades and aims to evaluate the diversity, abundance, richness and spatiotemporal variations of Cladocera within Samarra Impoundment water. The samples of these crustaceans were collected from three sites in the impoundment every two months between February 2023 and December 2024. We identified 19 taxa belonging to five Cladocerian families. The most abundant genera were Alona sp., Bosmina sp., Chydorus sp., Ceriodaphnia sp., Diaphanosoma sp., Daphnia sp. and Moina sp. The minimum and maximum densities were observed in spring and winter, respectively. The average values for evenness, richness and diversity indices were 0. 9, 0.82 and 0.88; 2.10, 1.98 and 1.71; 1.62, 1.55, and 1.43 bits/ind. at sites 1, 2 and 3, respectively. Seasonally, the lowest and highest values of richness and evenness indices were observed in summer and spring, respectively. The diversity index was observed in the summer and winter seasons. Furthermore, the analysis of the Jaccard similarity index indicated the highest value between the species at sites 1 and 3, reaching 39.98%.